Oral/oropharyngeal “selfies” in gay and bisexual men: a pilot study exploring oropharyngeal screening for HPV-related possible malignancies - Ross, Michael W.; Bennis, Sarah L.; Nichols, C. Mark; Zoschke, I. Niles; Wilkerson, J. Michael; Rosser, B. R. Simon; Stull, Cyndee L.; Nyitray, Alan G.; Flash, Charlene; Khariwala, Samir S. (Frontiers in Public Health, 2023)
Objectives: To determine the potential uptake and quality of oropharyngeal “selfies” taken by gay/bisexual men as a screening approach for HPV-associated oropharyngeal cancer Methods: From 1699 gay/bisexual men in the US surveyed about knowledge and attitudes to HPV-associated oropharyngeal cancer, a random sample of 320 men were invited to take an oropharyngeal “selfie” by smartphone and send it to the study website: 113 (35.5%) did so. Images were rated for quality by 3 healthcare professional raters blinded to each other’s rating, with an otolaryngologist as gold standard. In a second wave, those whose images were rated as unacceptable were sent a short instructional video and invited to send another image. Of the 65 invited, 46 did so. An additional 15.2% sent acceptable images. Results: 1121 men willing to participate in future study who believed they could take a quality “oral selfie” were potentially eligible for this activity. A random sample of 320 participated: 153 participants started (47.8%) and 113 participants (35.3%) submitted an image. Responders were more likely to be younger, have higher knowledge scores on oropharyngeal HPV related cancer, and have had HPV vaccination. There was high agreement between the 3 raters. Images were good/acceptable quality, 22.1%; oropharynx partially occluded, 29.2%; oropharynx not visible, 18.6%; image too dark, 21.2%; image too small, 8.8%. From the second wave request with instructional video, an additional 15.2% sent in quality images, with the remaining issues being partial occlusion of the tonsils by the tongue. Conclusions: A third of invited gay and bisexual men sent an oropharyngeal selfie image to the study website and 22% were clinically acceptable quality. Following an instructional video for poorer quality images, additional quality images were received. One barrier, partial occlusion of the oropharynx by the tongue, remained. Quality oropharyngeal “selfies” are obtainable online.